Impact of an Ultrasonically Activated Device in Robot-Assisted Distal Gastrectomy. Issue 6 (November 2017) - Hikage, Makoto; Tokunaga, Masanori; Makuuchi, Rie; Tanizawa, Yutaka; Bando, Etsuro; Kawamura, Taiichi; Terashima, Masanori
Abstract : Objective: Robot-assisted gastrectomy is increasingly used for the treatment of gastric cancer, although it remains a time-consuming procedure. An ultrasonically activated device might be useful to shorten operation times. This study therefore assessed the effect of ultrasonically activated device use on procedural times and on other early surgical outcomes. Methods: Consecutive patients (N = 42) who underwent robot-assisted distal gastrectomy for gastric cancer were included. Clinicopathological characteristics and early surgical outcomes were compared between robotic-assisted gastrectomy procedures using an ultrasonically activated device (U group, n = 21) and those without it (NU group, n = 21). Results: There were no significant differences in patient characteristics between the groups; however, the median operation time was significantly less in the U group than in the NU group (291 vs 351 minutes, P = 0.006). In detail, the median duration of console time until dividing the duodenum was less in the U group (70 vs 102 minutes, P < 0.001). Estimated blood loss, incidence of postoperative morbidity, and duration of postoperative hospital stay were not different between the groups. Conclusions: An ultrasonically activated device reduced the operation time of robot-assisted gastrectomy without increasing blood loss and morbidity.